DEVELOPMENT MONOPOLY MEDIA TO INCREASE STUDENT'S MOTIVATION STUDY OF SOCIAL SCIENCES IN MIDDLE SCHOOL - Ichmi Yani Arinda Rohmah (Jurnal Partisipatoris, 2020)
Research and development of Monopoly media is carried out using Borg and Gall product development procedures. The development of Monopoly learning media is carried out with the aim of increasing student learning motivation on social sciences material in the second semester of class VII at SMP Muhammadiyah 9 Surabaya. Media development is carried out through two validity tests, the results of the feasibility test show different values. The final results show that the developed learning media get 80% good and 90% very good, so in this case the Monopoly learning media in Social Sciences studies is suitable for student learning. Based on observations made by researchers shows after the application of Monopoly learning media, students have better motivation and focus than before applying Monopoly media.